Proceedings: International Regulatory Considerations on Development Pathways for Cell Therapies. (18th July 2014) - Feigal, Ellen G.; Tsokas, Katherine; Viswanathan, Sowmya; Zhang, Jiwen; Priest, Catherine; Pearce, Jonathan; Mount, Natalie
Abstract : The International Workshop on Regulatory Pathways for Cell Therapies was convened in September 2013 to discuss the nature of regenerative medicine as a rapidly evolving field with novel scientific and regulatory challenges and to highlight opportunities for potential convergence between different regulatory bodies that might assist the field's development. Discussions generated potentially actionable steps in five main areas that could mitigate cell therapy development pathway risk and accelerate moving promising therapies to patients. Abstract: Regenerative medicine is a rapidly evolving field that faces novel scientific and regulatory challenges. In September 2013, the International Workshop on Regulatory Pathways for Cell Therapies was convened to discuss the nature of these challenges and potential solutions and to highlight opportunities for potential convergence between different regulatory bodies that might assist the field's development. The workshop discussions generated potentially actionable steps in five main areas that could mitigate cell therapy development pathway risk and accelerate moving promising therapies to patients. These included the need for convergence of regulatory guidelines on donor eligibility and suitability of lines for use in clinical trials and subsequent commercialization for cell therapies to move forward on a global basis; the need to challenge and encourage investigators in the regenerative medicine field to share information and provide examples of comparability studies related to master cell banks; the need for convergence of guidelines across regulatory jurisdictions on requirements for tumorigenicity studies, based on particular cell types and on biodistribution studies; the need to increase transparency in sharing clinical trial information more broadly and disseminating results more rapidly; and the need to establish a forum for sharing the experiences of various approaches being developed to expedite regulatory approvals and access for patients to innovative cell and regenerative therapies in the different regulatory jurisdictions and to assess their potential strengths and weaknesses.